Características Epidemiológicas y Complicaciones de las Luxaciones de Hombro tratados con Reducción Cerrada - Floreano Mercedes, Jeiner Andersson (2019)
Objective: Describe the epidemiological characteristics and complications of shoulder dislocations treated with closed reduction at the Regional Teaching Hospital of Trujillo from 2016 to 2018. Materials and methods: Descriptive observational study. The statistical department's medical records and database were used to select epidemiological data and associated complications of 108 patients diagnosed with shoulder dislocation, which were recorded on a collection sheet previously designed. Results: 57% of dislocations correspond to the male sex, 39% of them belong to the second and third decades, the fall mechanism was found in 62%, 62% occurred in the right shoulder, 75% was made with a therapeutic vacuum less than one day and the comlic identified actions were: reluxation (25%) y fractured tubersity (32%). Conclusions: dislocations were most commonly identified in: male sex, under 40 years, low energy mechanisms, the right side turned out to be the most compromised and the most representative therapeutic vacuum was recorded in less than 1 day. The most common complications were relaxation y fractured tuberosity.